2018
DOI: 10.1590/fst.15017
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar affects the color change kinetics of sugarcane juice

Abstract: This study evaluated the influence of different Brazilian cultivars (RB867515/C1, SP813250/C2, RB92579/C3 and CTC02/C4) on unprocessed sugarcane juice quality by physicochemical, microbiological and enzymatic analysis. Color parameters were determined during six days at 10 °C. The experimental design was completely randomized with four treatments (cultivars) and three replicates. Significant differences were observed (p ≤ 0.05) among the juice samples from different cultivars. The pH values ranged from 5.09 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Minimal change colour change during processing is a very important trait for the food industry (Bomdespacho et al, 2018;Thakur et al, 1996). Colour changes of the sugarcane juice as a result of heat treatment for 5 and 15 minutes and ultrasonic treatment for 40 °C and 60 °C is displayed in Table 2.…”
Section: Effect Of Heat and Sonication Treatment On The Physicochemicmentioning
confidence: 99%
“…Minimal change colour change during processing is a very important trait for the food industry (Bomdespacho et al, 2018;Thakur et al, 1996). Colour changes of the sugarcane juice as a result of heat treatment for 5 and 15 minutes and ultrasonic treatment for 40 °C and 60 °C is displayed in Table 2.…”
Section: Effect Of Heat and Sonication Treatment On The Physicochemicmentioning
confidence: 99%
“…Andrade et al (2014) reported PPO and POD activities in the range of 3.7–40.6 U and from 3.4 to 148.6 U, respectively. Bomdespacho et al (2018) observed PPO activities in the range of 9.4–15.4 U in raw juice, while the POD activity ranged from 5.2 to 33.2 U. Bucheli and Robinson (1994) used chlorogenic acid as substrate to determine the PPO activity, and reported a greater PPO activity in the cane juice as compared to the use of others substrates. Catechol was the substrate herein used.…”
Section: Resultsmentioning
confidence: 99%
“…reported PPO and POD activities in the range of 3.7-40.6 U and from 3.4 to 148.6 U, respectively Bomdespacho et al (2018). observed PPO activities in the range of 9.4-15.4 U in raw juice, while the POD activity ranged from 5.2 to 33.2 U Bucheli and Robinson (1994).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…SCJ marketing and processing operations are quite a few because sugarcane fermentation begins immediately the following extraction as it contains 80% water and 20% total soluble solids (TSS) with a pH greater than 4.6 and water activity 0.99 aW (Abhilasha & Pal, 2018). The presence of carotenoids, anthocyanins, melanoidins, flavonoids, melanin, and substances from the alkaline oxidation of fructose in varying quantities in sugarcane affects its color, which consequently affects consumer appeal (Bomdespacho et al, 2018). Enzymatic browning is a significant contributor to SCJ degradation.…”
Section: Introductionmentioning
confidence: 99%